Micropoetics of the work and literary anthropology (to the problem of gastronomic codes of I. Franko’s short story “Pies with nuns”) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2021)
The article considers such an important aspect of the integrity of a literary work as micropoetics. The connection between anthropology and thestructure of artistic integrity is traced. The conclusion is made about the role of materialized and objective series of the work, its semiotic meanings, socio-cultural status. The theoretical concept is considered on the example of I. Franko’s short story “Pies with nuns”, in which the plot-forming are gastronomic codes. Food appears centrally with numerous additional semantic connotations, contextual meanings, and a powerful psychological connotation. Emphasis is placed on the anthropological characteristics of the motive of food, its close connection with the inner behavior of man, the cultural and historical epoch. Literary gastronomy as an aspect of micropoetics is also interpreted in the context of stereotypes as established patterns of perception of another, another, diﬀerent. Thus stereotypes are estimated according to laws of national literary process and have individual coloring in each epoch.Gastronomic codes are characterized by a powerful modeling function, able to reproduce the most general trends of socio-historical life. It is concludedthat this level of poetics is closely connected with otherlevels of the structure of a literary work.
Keywords: anthropology; micropoetics; integrity; food; literary gastronomy; behavior; humanities; sacralization; archetype